Pengaruh Media Pembelajaran Google Classroom Terhadap Motivasi Belajar Siswa SMK Negeri 2 Purwakarta Mata Pelajaran PAI Pada Masa Covid-19 - Nida Siti Maesaroh; Imam Tabroni; Didin Syaprudin (Paedagogie: Jurnal Pendidikan dan studi Islam, 2022)
SITIchangesin the learning system using media on the internet. Which has an impact on the learning process, and it is not uncommon for a decrease in student motivation to learn and a decrease in achievement in one school. This studyaims to measure the value of using the Google Classroom learning media and the value of motivation and to determine the effect of the Google Classroom learning media on the learning motivation of students at SMK Negeri 2 Purwakarta for PAI subjects during the Covid-19 period. The approachof this research is quantitative with the correlative method, the research subject is 55 respondents, the data collection technique is using a questionnaire. Based on the results of the questionnaire from 55 students' answers regarding the Google Classroom learning media, that the use of Google Classroom as a learning medium can have a good effect on students' learning motivation with an average value of 81.00%, referring to the percentage and assessment criteria, the figure is in the 63.00 interval. - 81.99 in the good category and students' learning motivation is considered very good with an average value of 82.45% of all questions, referring to the percentage and assessment criteria, the number is in the interval 82.00 - 100.00 with a very good category. The results of hypothesis testing obtained "r" count of 0.893. These values ​​are in the interval 0.80 – 1,000 very strongly correlated. The percentage of the relationship is 0.797 which implies that the influence of the Google Classroo learning media variable on the learning motivation variable is 79.7% and the remaining 20.3% is influenced by other factors. F valuecount of 207,813. While the Ftable with df1 = k – 1 (2 – 1 = 1) and df2 = 55 – 2 = 53 with an error rate of 5%, the Ftable is 4.02. Based on this comparison, Fcount > Ftable, so it can be concluded that Ho is rejected and Ha is accepted, meaning that there is an influence between the Google classroom learning media on the learning motivation of students at SMK Negeri 2 Purwakarta for PAI subjects during the covid-19 period.